Customer Satisfaction on How McDonald's Performs on Post-Pandemic - Oh, Zi Jian; Liem, Gai Sin; Han, Liew Chu; Xing, Liew Qiad; Yie, Liew Qian; Kang, Lim Boon; Rania, Hasna; Bahari, M. Hendis Mulya; Ainurridho, Dhani; Daifullah, Doly Difa (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
The Covid-19 has driven the entire planet to a dangerous tipping point, and no one is spared from this crisis, including our nation, Malaysia. Malaysia imposed the movement control order (MCO) on March 18, 2020, to blunt the exponential rise of Covid-19 cases and transition to the endemic phase of the Covid-19 pandemic on April 1, 2022. On account of that, this paper identifies customer satisfaction in the ways (social distancing, use of masks and hand sanitizers, contactless and cashless system, hygiene and cleanliness, and checking body temperature) McDonald’s adopted in Malaysia to surmount the outbreak of Covid-19. The researchers have collected primary data via Google Forms, with 150 participants partaking in this survey, and secondary data from different sources to conduct a deeper study on the research topic. Therein, this paper can enhance the understanding of how McDonald's performed post-pandemic. The researchers have used the IBM SPSS Statistic software to analyze the data collected. Overall, researchers find that most customers are satisfied with the measures taken by McDonald’s to combat Covid-19